Eficiência no uso da água em cultivares de feijão - Previl, Renan (2021)
Intrinsic water use efficiency (iWUE, the ratio between net photosynthetic rate and stomatal conductance) is a variable that has been considered useful for selecting drought-resistant material in plant breeding programs, presumably because this variable is not affected by environmental conditions, more particularly by the leaf-to-air vapor pressure deficit (VPDl), in detriment of another variable, the instantaneous water use efficiency (WUE, the ratio between net photosynthetic rate and transpiration rate) which is affected by VPDl. However, this response is not universal, and some species show variations in stomatal conductance to water vapor (gsw) and to CO2 (gsC) due to the effect of VPDl on the opening of stomata, which makes iWUE sensitive to VPDl in these plants. The objective of this research was to evaluate the VPDl effect on gsw in three wild varieties and one commercial cultivar of common bean. The research was divided into two stages. The first consisted of evaluating the sensitivity of gsw of plant materials to VPDl and its consequences on WUE and iWUE. The second consisted of the anatomical characterization of the variables that are used to estimate the gsw for these same plant materials, namely: the ostiole opening area, stomatal density and pore depth; and comparing these estimates with the gsw values obtained through instrumental measurements in order to identify possible compromises. As a result, it was found that all plant materials showed VPDldependent gsw, particularly due to the effect of VPDl on the opening area of the stomata. As a consequence, for these plants iWUE is not independent of VPDl. In the comparison of gsw measured instrumentally and estimated through anatomical variables, it was found that the values of the diffusion coefficients of water vapor through the stomata that are routinely used in scientific works are oversized and that the value of the maximum stomatal conductance obtained in these cases it is a theoretical value that must be taken with caution.